Distal Radius Salter-Harris III Transitional Fracture in an Adolescent Male - Adam Kurland; Brian Batko; Jeremy Hreha; Ashley Ignatiuk (Case Reports in Orthopedics)
In contrast to the well-described Tillaux fracture of the distal tibia, transitional fractures of the distal radius are exceedingly rare and have yet to be well described. Thus far, their presence in the literature has been limited to case reports and a singular series. None have involved a Salter-Harris III fracture pattern. We present the case of a 16-year-old male who sustained a Salter-Harris III transitional fracture of the distal radius with an associated ulnar styloid avulsion fracture secondary to a fall that was treated nonoperatively. Similar to the Tillaux fracture, examination of the distal radius transitional fracture should include computed tomography scan to better illustrate the pattern of injury and guide treatment.